The art of tomorrow - Hess, Barbara; Jackson, Gerrit (Berlin : Distanz, 2010)
Presents the work of around 80 contemporary artists.
Text English-German
boek
Keywords: Art, Modern -- 21st century -- Pictorial works; Artists -- 21st century